Incidence of mental retardation as compared with other psychiatric disorders and necessary support to persons placed at the Public Institution for Placement of Persons with Mental Disabilities „Drin“ Fojnica, Bosnia and Herzegovina - Edin Bjelošević; Amar Karahmet; Halima Hadžikapetanović; Sonja Bjelošević (Medicinski glasnik, 2016)
Aim: To compare the frequency of mental retardation with other psychiatric disorders at the Institute for Mentally Disabled Persons „Drin“ Fojnica, Bosnia and Herzegovina, to asses psychosocial condition and necessary support to persons with mental retardation. Methods: In this retrospective, descriptive and epidemiologic study neuropsychiatric findings and reports of the Institute’s social services of 527 residents (beneficiaries) were analyzed in the period 2013-2014 (age, gender, mobility, years of life spent in the Institute, visits of family members and close relatives, visits to families, mental retardation - degree, required support). Results: The research included 213 (40.42%) women and 314 (59.58%) men. The average age was 39.64 years. The average number of years spent in the Institute was 10.42.Fifty-four (25.47%) examinees with mental retardation had occasional visits to their families, while 69 (32.54%) had regular visits. Thirty-four (16.04%) examinees had mild mental retardation, 70 (33.02%) had moderate retardation, 52 (24.52%) were with severe, and 56 (26.42%) with profound retardation. It was found that 66 (31.13%) beneficiaries with the diagnosis of mental retardation completely depended on other persons. Conclusion: The degree of mental retardation has a direct impact on the process of resocialization. A very small number of people diagnosed with mental retardation had been successfully involved in the process of resocialization. It is necessary work intensively on thecreation of conditions for the realization of the Independent Living Support program, thus making a step forward to deinstitutionalization.
Keywords: support; rehabilitation; psychosis